Identification of a DOCK180-related Guanine Nucleotide Exchange Factor That Is Capable of Mediating a Positive Feedback Activation of Cdc42 - Lin, Qiong; Yang, Wannian; Baird, Daniel; Feng, Qiyu; Cerione, Richard A. (The Journal of biological chemistry, 2006)
Cdc42, a member of the Rho subfamily of small GTPases, influences a wide range of activities including the establishment of cell polarity, migration, and the regulation of cell growth and differentiation. Here we describe the identification of an ∼220-kDa protein that formed a stable complex with activated forms of Cdc42 and thereby showed characteristics of a downstream target/effector for this GTPase. However, molecular cloning of the cDNA encoding this protein (p220) revealed that it was highly related to Zizimin-1 and identical in sequence to a gene product in the data base designated DOCK11, which are members of the DOCK180 family of guanine nucleotide exchange factors (GEFs) for Cdc42 and Rac. Biochemical characterization shows that p220 is a specific GEF for Cdc42, with the GEF activity originating from its DHR2 (for DOCK homology region 2) domain. Nucleotide-depleted Cdc42 forms a stable complex with the DHR2 domain, whereas the binding of activated Cdc42 requires both the DHR2 domain and residues 66-126 within the amino-terminal portion of p220. Moreover, the full-length protein shows markedly higher GEF activity than the isolated DHR2 domain, whereas removal of the amino-terminal 126 amino acids necessary for binding-activated Cdc42 dramatically diminishes the activity. These and other results point to activated Cdc42 providing a positive feedback regulation of the GEF activity of p220. Thus, we refer to p220/DOCK11 as activated Cdc42-associated GEF, befitting its functional activity.